Analysis of the results of the introduction of the experimental methodology for the integrated development of motor qualities and the assimilation of elements of the technique of young weightlifters 10–12 years - Bugaev, Eugen; Dzhym, Viktor; Boltenkova, Olga (Sloboz͡h︡ansʹkyĭ naukovo-sportyvnyĭ visnyk, 2018)
Purpose: revealing the influence of the experimental technique on the development of motor qualities and the assimilation of elements of the technique of young weightlifters 10–12 years. Material & Methods: in this study young men of 10–12 years engaged in weight lifting sections in the Youth Sports School of KhTP, as well as in the sports school No. 2 of Kharkov took part. The subjects were divided into two groups, control and experimental, for 24 athletes 10–12 years in each. At the time of the experiment, there was no significant difference between the groups in the tests that were used to determine the level of physical and technical preparedness. Results: experimental technique of complex development of impellent qualities and mastering of elements of technics of weightlifting of young sportsmen is presented. The combination of the assimilation of elements of technics and physical exercises is more effective the accentuated decision of each of the elements. Conclusions: it was found that the combination of training in weightlifting techniques with the development of motor skills in the experimental group made it possible to more effectively solve both problems - the assimilation of the element of technics and the development of motor qualities.